POLA ASUH IBU PEKERJA DALAM MEMBENTUK KEMANDIRIAN ANAK USIA DINI DI KELOMPOK BERMAIN AL HIKMAH KECAMATAN WALANTAKA KOTA SERANG - Holida, Ida (Jurnal Anak Bangsa, 2024)
Independence is very important for early childhood, therefore to foster early childhood independence is greatly influenced by parenting patterns, while in Kober Al-Hikmah there are several working mothers. The purpose of this study was to determine the extent to which the parenting patterns applied by working mothers in shaping the independence of early childhood. The type of research used by researchers is a qualitative method using a case study approach. The subjects of this study were three working mothers who had early childhood children aged 5-6 years in Kober Al-Hikmah. In this study, researchers used data collection techniques in the form of interviews and documentation. Data analysis techniques through several stages including 1. investigating data, 2. presenting data, and 3. Drawing conclusions. The results of this study indicate that the parenting patterns applied by three working mothers in shaping the independence of early childhood by providing attention, providing examples and good behavior and discipline will shape the independence of early childhood